IMPROVEMENT OF ELEMENTARY SCHOOL STUDENTS’ COMPETENCE OF READING COMPREHENSION THROUGH GENERATIVE LEARNING MODEL - Asep Saepurokhman (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
ABSTRACT Reading comprehension is a competence that everyone has to possess. It can broaden human’s insight in that we will not be left behind as time goes so fast. One of the teachers’ efforts as to enhance the reading comprehension competence is to apply a learning model that is able to explore a lot of students’ potency. The learning model considered to be capable of developing the students’ creative-thinking is a generative model. Based on the result of data analysis, it is known that the process of reading-comprehension learning runs well in full activity of students. The students’ tendency to the learning of reading comprehension using such a model is positive in the means of 75.10%. The generative learning model succeeds in enhancing the students’ competence of reading comprehension. The means of score before the treatment is only 53.80%, whereas after the treatment it gets 72% in which the index gain is 0.41 and it is categorized into mediocre. There is difference of reading-comprehension competence between the use of generative learning model and conventional model. It is proven by t-test, indicating that t-observed is higher than t-table. Therefore, the generative learning model is effective and reasonable to use for the teachers in the improvement of stduents’ reading-comprehension competence.